Evaluation of GAD67 immunoreactivity in the region of substantia nigra pars reticulata in resistance to development of convulsive seizure in genetic absence epilepsy rats - ONAT, FİLİZ; GÜLÇEBİ İDRİZ OĞLU, MEDİNE; KARAMAHMUTOĞLU, TUĞBA (KARE PUBL, 2016)
OBJECTIVE: Nonconvulsive absence epilepsy and convulsive epilepsy seizures are rarely seen in the same patient. It has been demonstrated that there is a resistance to development of convulsive seizures in genetic absence epilepsy models. The present study investigated glutamic acid decarboxylase (GAD) immunoreactivity in the brain region related to the interaction of these two seizure types, namely substantia nigra pars reticulata (SNR) subregions, SNRantenor and SNRpostenor. METHODS: Nonepileptic adult male Wistar rats and Genetic Absence Epilepsy Rats from Strasbourg (GAERS) were used. Experimental groups of Wistar and GAERS were electrically stimulated for kindling model to induce convulsive epileptic seizures. An electrical stimulation cannula was stereotaxically implanted to the basolateral amygdala and recording electrodes were placed on the cortex. Sagittal sections of SNR were used to evaluate immunohistochemical reaction. Sections were incubated with anti-GAD67 antibody. Densitometric analysis of GAD67 immunoreactive neurons was performed using photographs of stained sections. One-way analysis of variance and post hoc Bonferroni test were used for statistical analysis of the data. RESULTS: There was no difference in GAD67 immunoreactivity of SNR subregions of control Wistar and control GAERS. An increase in GAD67 immunoreactivity was detected in SNRposterior subregion of stimulated Wistar rats, whereas there was a decrease in GAD67 immunoreactivity in SNRposterior of stimulated GAERS. The difference in GAD67 immunoreactivity between these two groups was statistically significant. CONCLUSION: Level of synthetized gamma-aminobutyric acid in SNRposterior subregion plays an important role in the interaction of nonconvulsive absence epilepsy seizures and convulsive epilepsy seizures.
Keywords: Epilepsy; GAERS; gamma-aminobutyric acid; immunohistochemistry; GAMMA-AMINOBUTYRIC-ACID; TEMPORAL-LOBE EPILEPSY; ELECTRICAL-STIMULATION; MECHANISMS; THRESHOLD; NEURONS; MODEL